2003
DOI: 10.1007/bf02296180
|View full text |Cite
|
Sign up to set email alerts
|

The effect of health investment on growth: A causality analysis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 26 publications
2
27
0
1
Order By: Relevance
“…We also considered the growth rates of each country's export partners as used by Acemoglu et al (2008) and the modified version suggested by Burke (2012). Other variables relating to long-term growth rates such as the number of hospital beds, measuring health expenditures and thus driving growth (Rivera and Currais, 2003), were not available for the entire period, while information pertaining to intellectual property rights, such as the Ginarte-Park Index was not available for a large number of countries.…”
Section: Reverse Causalitymentioning
confidence: 99%
“…We also considered the growth rates of each country's export partners as used by Acemoglu et al (2008) and the modified version suggested by Burke (2012). Other variables relating to long-term growth rates such as the number of hospital beds, measuring health expenditures and thus driving growth (Rivera and Currais, 2003), were not available for the entire period, while information pertaining to intellectual property rights, such as the Ginarte-Park Index was not available for a large number of countries.…”
Section: Reverse Causalitymentioning
confidence: 99%
“…It is also an important determinant of the productivity of human capital. World Bank and others have drawn attention to health as a factor in economic development [87,88]. Fogel found that one third or more of the economic growth in England over the last two centuries was attributable to improvements in nutrition which result in greater height and weight [89].…”
Section: Income Inequalitiesmentioning
confidence: 99%
“…High inequality reduces economic development by slowing poverty eradication, retarding investments in education, and inhibiting entrepreneurship [101]. World Bank and others have drawn attention to health as a factor in economic development [88].…”
Section: Income Inequalitiesmentioning
confidence: 99%
“…Here, we briefly summarize the results of recent literature which examine the relationship between health and economic growth. Rivera and Currais (2003) investigate the influence of health investment on productivity in OECD countries over the period 1960-2000. The authors estimate an Augmented Solow Model by using ordinary least squares and two stages least squares estimators and find that health expenditure has a positive effect on economic growth (Rivera and Currais, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are quite a few studies which investigate the impact of health/health care expenditure on economic growth in the existing literature. These studies generally find that health/health care expenditure has a positive influence on economic growth (see for instance; Rivera and Currais, 2003;Bloom et al, 2004 andLI andHuang, 2009). However, the number of studies which analyse the causality between health care expenditure and economic growth is very low.…”
Section: Introductionmentioning
confidence: 99%